Hans-Jörg Uther, The types of international folktales. A classification and bibliography, Helsinki, Academia Scientiarum Fennica, 2004, 3 volumes: FFC 284 (619 pages) + FFC 285 (536 pages) + FFC (284 pages) - Correia, Paulo (2013)
For all those who, like ourselves, carried the task of classifying a regional corpus of folktales, this third revision of the Aarne-Thompson catalogue was the best news we could hope for. In fact we were all acutely aware that the “AT” was a research tool with as many qualities as it raised problems. One of these was the gap between the aim of its scope —to cover the whole folktale world— and the poor representation of certain geographic areas in terms of versions included.